The effect of diet upon serum concentrations of theophylline. - Thompson, P J (1983)
Eight patients with airways obstruction were investigated to determine if dietary components had any significant effect upon serum concentrations of theophylline when taking a slow release formulation. A high carbohydrate, low protein diet, given for 1 week, resulted in the area under the concentration time curve for 12 h being 33.3% greater than a high protein low carbohydrate diet given under the same conditions. In contrast to two previous studies no significant effect upon the elimination half-life was detected after changing from one diet to the other and an effect of dietary components upon absorption and/or distribution needs to be considered. Morning and afternoon trough levels were significantly different from each other on both diets suggesting that theophylline kinetics are different at night. Individualising of theophylline dosing is particularly needed when treating patients on a varied dietary intake.